SELECTIVE ATTENTION MAHASISWA DALAM SITUASI DISTRAKSI SENSORIK: STUDI KASUS RESPONS TERHADAP STIMULUS MAKAN DAN MUSIK - Nurlaelasari, Nurlaelasari; Ghautama, Hellen Lie Grace; Izzuddin, Fathan Muhammad; Dahlan, Tina Hayati; Sukmana, Cucu (Jurnal Visi Ilmu Pendidikan, 2026)
This study explores how university students experience and manage selective attention in learning situations accompanied by sensory distractions such as music and food. Employing a qualitative exploratory case study design, three students participated in four reading simulations involving different text types and sensory stimuli. The findings reveal that selective attention is an adaptive process shaped by emotional states, sensory preferences, and metacognitive strategies. Preferred music enhanced emotional comfort and supported focus, while disliked music and crunchy foods disrupted cognitive processing. The type of text also played a role"”narrative texts in the native language were easier to comprehend than academic texts in a foreign language. Emotions emerged as a key mediator between distraction and comprehension, and cognitive flexibility proved essential in maintaining learning performance under multitasking conditions. These findings offer valuable insights into the complexities of attention in everyday learning environments marked by frequent distractions.